Reserve-Dependent Benefits and Costs in Life and Health Insurance Contracts - Marcus C. Christiansen; Michel M. Denuit; Jan Dhaene (Tinbergen Institute, 2014)
Premiums and benefits associated with traditional life insurance contracts are usually specified as fixed amounts in policy conditions. However, reserve-dependent surrender values and reserve-dependent expenses are common in insurance practice. The famous Cantelli theorem in life insurance ensures that under appropriate assumptions surrendering can be ignored in reserve calculations provided the surrender payment equals the accumulated reserve. In this paper, more complex reserve-dependent payment patterns are considered, in line with insurance practice. Explicit formulas are derived for the corresponding reserve.
Keywords: 330; life insurance; multistate models; Markov process; surrender value; Cantelli theorem